A conceptual framework for the quality assurance of programme design at the Durban University of Technology - Sattar, Kalawathie (South African Journal of Higher Education, 2016)
At the end of 2010 the Durban University of Technology initiated a Curriculum Renewal Project, central to which is the aspiration to become a student centred university through the transformation of teaching and learning and the promotion of quality enhancement. However, the current realities for curriculum development and quality assurance at the university cannot be disengaged from a context shaped by influences such as the history of the technikon sector, the merger, and a changing external regulatory environment. The requirements of national agencies influence the current approaches to curriculum development and the quality assurance thereof. To address these contextual factors, a conceptual framework for the quality assurance of programme design has been developed which favourably positions the university to respond to internal and external requirements. The opportunities that will contribute to the successful outcome of the Curriculum Renewal project as well as the potential challenges are elaborated. Keywords: quality assurance, quality enhancement, curriculum development, university of technology, technikons, merger, external regulation.